A rare case of retroperitoneal tumor diagnosed as adrenal ancient schwannoma - Lalithya,; Jadhav, Kiran P.; Beedkar, Anant N. (International Journal of Research in Medical Sciences, 2024)
Retroperitoneal ancient schwannoma is a rare condition. Schwannomas are mostly seen arising from head and neck, flexor aspects of extremities, with an incidence 0.7–2.7%. Other sites of schwannoma are rare with few recorded cases. Retroperitoneal schwannomas (RPS) are relatively rare and constitute only 3% of all schwannomas and 4% of retroperitoneal tumours. Diagnosis is mostly made by histopathology and immunohistochemistry (IHC). Here we report a case of 60-year female with retroperitoneal ancient schwannoma, who presented with chronic abdominal pain.